Characterization and crystallization kinetics of sputtered NiSi thin films for blue laser optical recording application. (June 2017) - Ou, Sin-Liang; Chen, Sheng-Chi; Lin, Yan-Cheng; Lin, Po-Chun; Wen, Chao-Kuang; Chuang, Tung-Han
Abstract: In this study, Ni31 Si69, Ni43 Si57 and Ni63 Si37 thin films with the thickness of 16 nm were deposited at room temperature by co-sputtering using Ni and Si targets. From the result of reflectivity-temperature measurement, it was found the NiSi layers possessed two temperature ranges of reflectivity change, i.e. 150–270 °C and 320–370 °C. Microstructural analysis indicated that the NiSi2 nano-crystalline phase was formed in the as-deposited state. After annealing at 270 and 500 °C, the crystallinity of NiSi2 phase was improved and the Ni2 Si phase appeared, respectively. By measuring the optical reflectivity at a wavelength of 405 nm, the optical contrasts of these films before and after annealing at 270 °C were determined to be 24%, 16% and 26% with the Ni contents of 31, 43 and 63 at.%, respectively. The optimum jitter values of Ni31 Si69 blu-ray disc were 7.7% at 5.7 mW and 8.2% at 7 mW, respectively, for 1× and 2× recording speeds. It reveals that the NiSi films have high potential in the application of blue laser recording media. Highlights: The 16-nm-thick Ni31 Si69, Ni43 Si57 and Ni63 Si37 films were deposited by sputtering. The microstructures and recording characteristics of these films were investigated. The NiSi layers possessed two temperature ranges of reflectivity change. The Ni31 Si69 thin film was suitable for the recording layer of blu-ray disc. Optimum jitter value of the Ni31 Si69 blu-ray disc is 7.7% for 1× recording speed.